The phrase Imam Muslim is a chain of narrators located next to an Isnad; an "analytical study" - Abu Tarboush, Rama (Jordan Journal of Islamic Studies, 2023)
This research attempts to understand what is meant by the term Imam Muslim, which he mentioned in the introduction to his Sahih when it comes to his method of repetition. It is the subject of the problem, as the scholars differed on its concept. Some of them carried it on the linguistic meaning, and some of them carried it on the idiomatic meaning of the modernists, which led to restricting the reason for the repetition of the chain of narrators in Sahih Muslim,This research aims to look at the scholars ’interpretations of this phrase, and then compare it with its making within the correct one when it is repeated for the chain of narrators, in order to find the right opinion on this issue. Different, either explanatory or non-explanatory.